Around the world in 80 days - Verne, Jules 1828-1905 (Penguin Books, 2004)
In 1872, English gentleman Phileas Fogg has many adventures as he tries to win a bet that he can travel around the world in eighty days. Includes a foreword by Laurence Yep and reading group guide.